Compostos de coordenação envolvendo aroil(N,N-dialquil-calcogenoureias) monopodais e bipodais - Schwade, Vânia Denise (2014)
This work presentes the study realized with monopodal and bipodal aroyl(N,N-dialkylchalcogenoureas) involving different metallic ions to obtain mononuclear, dinuclear and trinuclear compounds. The compounds were characterized by X-ray diffraction, 1H NMR, I.R., ESI+ MS and elemental analysis. In the first part, the chemistry of aroyl(N,N-dialkylchalcogenoureas) with {ReVO}3+ was investigated, where mononuclear and dinuclear compounds were obtained. In the second part, the chemistry of isophthaloylbis(N,N-diethylchalcogenoureas) was investigated against different metallic ions. Dinuclear complexes of AuI, CuII, HgII and InIII, and polymeric compounds with PbII and SnII were obtained. Compounds were also obtained with CuI and TeII. The structural analysis of the AuI, CuII, PbII and InIII compounds with isophthaloylbis(N,N-diethylthiourea), H2L1, have shown that the ligand can exhibit different orientations of the arms‟ to make bis(bidentate) chelate coordination, by the oxygen and sulphur atoms, or bis(monodentate), by the sulphur atoms. These orientations occur due the metal characteristics, as geometry or the influency of the lone pair of electrons. The third part was focused in exploring the synthesis of trinuclear compounds using combinations of metals with dipicolinoylbis(N,N-diethylchalcogenoureas). With the derivatized ligand, 4-chlorodipicolinoylbis(N,N-diethylthiourea), H2L4, trinuclear [MIIBaIIMII] and [MIIGdIIIMII] (where MII = Mn, Co) compounds were obtained; and with the dipicolinoylbis(N,N-diethylselenourea), H2L5, the compounds [MnIIBaIIMnII] and [MIISmIIIMII] (MII = Mn, Co) were obtained. The composition of these compounds for the charge compensation follows that observed for the known compounds with the dipicolinoylbis(N,N-diethylthiourea) ligand, H2L2, in the way that, depending on the combination of metals used, two or three bis(chalcogenourea) anions are involved, where also acetate and/or chloride anions can be involved. The derivatization (additional Cl atom in the pyridine ring of the ligand molecule) led to the connection of the trinuclear molecules due to Ba∙∙∙Cl interactions, verified by the structural analysis of one compound. With the H2L2 and H2L4 ligands the incorporation of PbII in the trinuclear systems was explored, and [PbIIBaIIPbII] compounds were obtained. In these compounds the PbII metallic centers are located in the border positions by the chelate S,O coordination of three bis(thioureato) anions. On the other hand, [MIIPbIIMII] compounds were obtained for MII = Mn and Ni with H2L2, in which PbII is located in the central cavity formed by the S,O chelate coordination to the MnII and NiII metallic centers. However, from the combination PbII/NiII, a tetranuclear compound was also obtained, leading to a discussion of radius ratio between the metals as an aspect to be considered to obtain trinuclear systems, seeking the alignment of the metallic centers in the complexes.